2017
DOI: 10.13057/biodiv/d180410
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Diversity of tropical plants and their attractant properties for subterranean termite Coptotermes curvignathus

Abstract: Indrayani Y, Muin M, Yoshimura T. 2017. Short communication: Diversity of tropical plants and their attractant properties for subterranean termite Coptotermes curvignathus. Biodiversitas 18: 1353-1357. The effectiveness of bio-based attractant from different leaves of tropical plants on subterranean termites Coptotermes curvignathus was examined under laboratory conditions. Five kinds of leaves of tropical plant such as cajuput (Melaleuca leucadendron L.), cinnamon (Cinnamomum burmannii (Nees & Th. Nees) N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The bait compositions showed that those containing eucalyptus leaves and cardboard led to a higher soil pH compared to containing paper only nor paper and eucalyptus. This finding is supported by the research carried out by Indrayani et al (2017bIndrayani et al ( , 2018, which stated eucalyptus leaf extract can be used as an attractant for termites.…”
Section: Soil Acidity (Ph)supporting
confidence: 66%
“…The bait compositions showed that those containing eucalyptus leaves and cardboard led to a higher soil pH compared to containing paper only nor paper and eucalyptus. This finding is supported by the research carried out by Indrayani et al (2017bIndrayani et al ( , 2018, which stated eucalyptus leaf extract can be used as an attractant for termites.…”
Section: Soil Acidity (Ph)supporting
confidence: 66%
“…Furthermore, previous data have shown that the crude extracts of S. aromaticum, M. leucadendra, and C. burmannii contain eugenol. GCMS analysis showed eugenol in each crude extract used in this study as follows: S. aromaticum (7.92%), C. burmannii (4.64%), and M. leucadendra, (3.36%), while the crude extract of the other two plant species contained derivatives of eugenol such as methyl eugenol (2.24%) in O. sanctum and acetyl eugenol in S. polyanthum (6.54%) (Indrayani et al 2017). The result of this study confirms that M. leucadendra crude extract, which is the most attractive to C. formosanus, has the lowest amount of eugenol.…”
Section: Trail Followingmentioning
confidence: 72%
“…Leaf extracts from the following five tropical plant species were prepared according to Indrayani et al (2017) Prior to the extraction, the plant leaves were airdried for 3 days and crosscut into small segments. The extraction was conducted with 70% ethanol solution for three 24-hours, and then rotary evaporated at 60°C for two 24-hour periods until the extract became a gel.…”
Section: Extracts and Treatmentsmentioning
confidence: 99%
“…On the other hand, the wetness and dryness conditions in the structures cause the wood material to decay. Indonesia's climate and soil conditions are very supportive of termite life [12].…”
Section: A Resultsmentioning
confidence: 99%
“…In the meantime, specific material for the support structures used second-class wood such as Jelutung, Selimpau, Rengas, etc. It is found that as many as 10 termite species were detected through a survey conducted on buildings in West Kalimantan, particularly in Pontianak [12]. These species are Nasutitermes Havilandi, Cryptotermes sp.…”
Section: A Resultsmentioning
confidence: 99%